Value of application of insights from Big Data Analytics on transformation of agriculture: case of farmers subscribed to Mkulima Techie Kenya - Okumu, Millicent (Strathmore University, 2021)
The application of big data analytics in agriculture is a revolution that has the potential to transform agriculture from being process driven to being data driven. Transformation of agriculture is defined as a process that involves gradual shifts in the production, from a traditional concept to a modern one resulting in change from a subsistence oriented monoculture system to a diversified and market oriented production system. The objectives of the study were to demonstrate the application of Big Data Analytics, determine the effect of usage of insights from Big Data Analytics and to determine the barriers in application of Big Data Analytics within a smallholder farmer setting. The study applied a mixed methods approach to investigate the value big data analytics has on transformation of agriculture. Data was collected using structured questionnaires from 282 respondents and key informant interviews. The inferential analysis tools applied included correlation analysis and logistic regression analysis. From this study, the findings reveal that there was a significant association between insights from big data analytics and value derived which facilitated transformation of agriculture in terms of income and yield for farmers. For the practitioners, researchers and policy makers in the agricultural industry this study provide guidelines to mitigate challenges in implementation and contributing to the broader discussion on the opportunities provided by a data driven agricultural industry. The limitations also help uncover future research courses in order to achieve better knowledge.
A Dissertation submitted in partial fulfillment for the award of the degree of Master of Management in Agribusiness, Strathmore University
Keywords: Big Data Analytics; Value; Agricultural transformation; Smallholder farmer